Bimbingan Kelompok dalam Kegiatan Organisasi Untuk Meningkatkan Kepekaan Sosial Mahasiswa - Fitriani, Dian; Arifin, Isep Zaenal; Tajiri, Hajir (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2024)
The purpose of this study was to increase the social sensitivity of Ika Darma Ayu UIN SGD Bandung Commisariat members through work programs, implementation processes and the results of group guidance to increase social sensitivity of Ika Darma Ayu members, UIN SGD Bandung Commissariat. The method used is qualitative by explaining group guidance to increase students' social sensitivity. The data collection techniques used are observation, interviews and documentation studies directly with members of the organization Ika Darma Ayu Komisariat UIN SGD Bandung. The results of this study indicate that Group Guidance in regional organizational activities is said to be successful because it experiences changes in social sensitivity attitudes in the form of empathy, cooperation, helping, and respecting others.